Analisis Kesulitan Siswa Dalam Menulis Puisi Serta Implikasinya Dalam Pengajaran Bahasa Indonesia Di Kelas VII SMP Negeri 1 Siberut Utara Kabupaten Kepulauan Mentawai - Najmi Hayati; Susanti Marisya; Odilia (JURNAL ARMADA PENDIDIKAN, 2023)
This study aims to analyze seventh-grade students’ difficulties in writing poetry and their implications for Indonesian language instruction at SMP Negeri 1 Siberut Utara, Kepulauan Mentawai Regency. The research employed a qualitative approach using a descriptive method. The participants were seventh-grade students. Data were collected through a poetry-writing test. Data trustworthiness was strengthened through triangulation. Poetry analysis used a modified rubric adapted from Nurgiyantoro (2016), covering four assessment aspects: diction, imagination, figurative language, and theme. The findings indicate that students experienced difficulties across all four aspects. In terms of diction, difficulties were reflected in inaccurate word relationships and less engaging word choices. Regarding imagination, students were not yet able to develop imagery and poetic visualization adequately. For figurative language, students faced obstacles in using figures of speech as a distinctive feature of poetry. With respect to theme, students had difficulty determining a clear and consistent theme. The study recommends more structured poetry-writing instruction focusing on diction selection, imagery development, figurative language use, and theme determination, supported by the use of model poems, concrete examples, and specific feedback for each assessment aspect.